Energy harvesting from high-rise buildings by a piezoelectric harvester device. (15th December 2015) - Xie, X.D.; Wang, Q.; Wang, S.J.
Abstract: A novel piezoelectric technology of harvesting energy from high-rise buildings is developed. While being used to harness vibration energy of a building, the technology is also helpful to dissipate vibration of the building by the designed piezoelectric harvester as a tuned mass damper. The piezoelectric harvester device is made of two groups of series piezoelectric generators connected by a shared shaft. The shaft is driven by a linking rod hinged on a proof mass on the tip of a cantilever fixed on the roof of the building. The influences of some practical considerations, such as the mass ratio of the proof mass to the main structure, the ratios of the length and flexural rigidity of the cantilever to those of the main structure, on the root mean square (RMS) of the generated electric power and the energy harvesting efficiency of the piezoelectric harvester device are discussed. The research provides a new method for an efficient and practical energy harvesting from high-rise buildings by piezoelectric harvesters. Highlights: A new piezoelectric technology in energy harvesting from high-rise buildings is introduced. A new mathematics model to calculate the energy harvested by the piezoelectric device is developed. A novel efficient design of the piezoelectric harvester device in provided. An electric power up to 432 MW under a seismic excitation at a frequency of 30 rad/s is achieved.